Reliability and discriminative power of soccer-specific field tests and skill index in young soccer players - Dardouri, W.; Amin Selmi, M.; Haj Sassi, R.; Gharbi, Z.; Rebhi, A.; Moalla, W. (Science & Sports, 2014)
Purpose: To examine the reliability and construct validity of straight sprint, agility, slalom dribble tests and skill index in young soccer players. Methods: Ninety-two male soccer players (age: 14.2 ± 0.6 years; body mass: 54.0 ± 8.9 kg; height: 166.3 ± 9.4 cm; body mass index: 19.4 ± 1.7 kg/m2) participated in this study. They were assigned to either two groups G1 or G2 according to their experience and competition levels. After familiarization, two trial sessions of three tests of sprint were administered: straight sprint (SS), agility test (AT) and slalom dribble test (SDT). Skill index (SI) was calculated as the ratio between AT and SDT. Results: Reliability of SS, AT, SDT performances and SI were very good, with intraclass correlation coefficient greater than 0.80, CV less than 5%, low bias and small ratio limits of agreement. Areas under the receiver operating characteristics curves (ROC) were 0.555 (95% CI: 0.448-0.659), 0.851 (95% CI: 0.762-0.917), 0.913 (95% CI: 0.836-0.962) and 0.629 (95% CI: 0.522-0.727) for SS, AT, SDT and SI, respectively. Conclusions: Results demonstrated that the three tests and SI were reliable but only AT, SDT and SI could discriminate between the levels of players` ability. They could be used for soccer-specific skills assessments and selection process of young soccer players.